Penerapan Metode IPA dan PGCV untuk Menganalisis Kualitas Layanan PT. Bank X berdasarkan Dimensi Servqual - Howin, Rikko; Prasetya, Wibawa (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
The bank is an institution that usually keeps people's money and redistributes it, as well as providing other services. The quality of service at the bank is important in order to compete well in the banking industry. This study aims to determine customer satisfaction, priority improvements needed to increase customer satisfaction. The data processing of this research begins with the validity and reliability test of the questionnaire, then continues with data processing using the SERVQUAL, IPA, and PGCV methods. In the SERVQUAL method there are a total of 22 attributes, for the tangible dimension it has 9 attributes, then the reliability dimension has 2 attributes, Furthermore, the responsiveness dimension has 4 attributes, the assurance dimension has 3 attributes, and finally the empathy dimension has 4 attributes. The result of Service Quality data processing, as a whole has a gap minus value. The results are then processed by the IPA method and the results show that six attributes are in the first quadrant (priority recovery), three attributes are in the second quadrant, one attribute is in the third quadrant, twelve attributes are in the fourth quadrant. The results of data processing using the IPA method, then continued with data processing using the PGCV method, and the results show that there are six attributes listed in the order of priority, with the highest PGCV score statement, namely the item